EFFECTIVENESS OF THE DAIRY FARMERS' PARTNERSHIP PROGRAM IN SAPI MERAPI SEJAHTERA COOPERATIVE (SAMESTA) YOGYAKARTA - Sari, Agil Anita; Gayatri, Siwi; Prayoga, Kadhung (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
This research is undermined by the fact that the research site is a milk cooperative established as an attempt to revive the post-disaster economy in the region. In accordance with its initial purpose of helping to improve the economy of the partners, the study aims to describe the implementation of partnerships and analyze the effectiveness of partnership of dairy farmers in the Samesta Corporation of Yogyakarta. The research location is in Samesta Company, Sleman District, Yogyakarta and carried out in January to February 2024. The research method used is a survey method with a method of purposive sampling. The sample farmer involved is a farmer who is still active depositing milk and following the cooperative activities of as many as 100 farmers who are scattered in the Cangkringan and Pakem districts. While the method of analysis used is descriptive analysis related to the implementation of the partnership program and descripative statistics to explain the effectiveness of the program. The findings show that the partnership program is conducted to empower the partner farmer as a member of the cooperative, supported by feed credit programmes, the development of compost and biogas, as well as bull loans. The form of partnership that runs is a core-plasma partnership. The constraints in the partnership program being run include productivity constraint, improved medical services for livestock, partner farmer confidence, and information transfer processes. Program effectiveness results measured on the basis of program understanding indicators, timeliness, target accuracy, target achievement, and real change indicate effectivency values of 64.30% and are categorized as effective so that the program can be continued.